2010
DOI: 10.1007/s12264-010-0410-9
|View full text |Cite|
|
Sign up to set email alerts
|

Progressive changes of orexin system in a rat model of 6-hydroxydopamineinduced Parkinson’s disease

Abstract: Objective Sleep disturbance, which is characterized by excessive daytime sleepiness and sleep attacks, is frequently observed in patients with Parkinson's disease (PD). Loss of orexin neurons in hypothalamus and the resultant decreased level of orexin in cerebrospinal fluid (CSF) found in narcolepsy patients may also play an essential role in the pathogenesis of sleep disturbance. The present study aimed to investigate the possible changes in the orexin system during PD progression. Methods After the establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…The orexin system develops very early in vivo (Van den Pol et al 2001 ; Stoyanova et al 2010 ); therefore the early expression of OR1 which we observed already at 1 DIV could be another indication for the importance of orexinergic input in developing networks. This observation is in accordance with the findings that the human sleep disorder, narcolepsy, as well as different neurodegenerative diseases, were recently related to a massive reduction or deficit of orexins and their receptors and a decreased level of OXA in the cerebrospinal fluid (Cui et al 2010 ; Friedman et al 2007 ; Petersén et al 2005 ; Ripley et al 2001 ). Experiments with transient common carotid artery occlusion in mice demonstrated increased levels of OXA and OR1 after ischemia (Nakamachi et al 2005 ).…”
Section: Discussionsupporting
confidence: 90%
“…The orexin system develops very early in vivo (Van den Pol et al 2001 ; Stoyanova et al 2010 ); therefore the early expression of OR1 which we observed already at 1 DIV could be another indication for the importance of orexinergic input in developing networks. This observation is in accordance with the findings that the human sleep disorder, narcolepsy, as well as different neurodegenerative diseases, were recently related to a massive reduction or deficit of orexins and their receptors and a decreased level of OXA in the cerebrospinal fluid (Cui et al 2010 ; Friedman et al 2007 ; Petersén et al 2005 ; Ripley et al 2001 ). Experiments with transient common carotid artery occlusion in mice demonstrated increased levels of OXA and OR1 after ischemia (Nakamachi et al 2005 ).…”
Section: Discussionsupporting
confidence: 90%
“…It was reported that parkinsonian patients display significant loss of orexinergic neurons in post-mortem exams ( Fronczek et al, 2007 ; Thannickal et al, 2007 ). Experiments with 6-hydroxydopamine (6-OHDA)-induced rat model of PD revealed that the number of orexinergic neurons in the lateral hypothalamus decreases significantly ( Cui et al, 2010 ). Furthermore, the orexin levels in plasma and cerebrospinal fluid decrease dramatically in parkinsonian patients ( Drouot et al, 2003 ; Fronczek et al, 2007 ; Thannickal et al, 2007 ; Baumann et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies in rats showed that injection of 6-OHDA in the DS or MFB decreases the number of orexin neurons in the LH (Cui et al, 2010; Oliveira et al, 2018), thereby reproducing a similar damage described in PD (Maeda et al, 2006; Thannickal et al, 2007). This loss was paralleled by reduced baseline respiratory frequency during sleep in the light-on period (Oliveira et al, 2018), a condition reminiscent of breathing disturbances and sleep apnea observed in PD patients (Mery et al, 2017; Videnovic, 2017).…”
Section: Introductionmentioning
confidence: 56%
“…Combined loss of dopamine, noradrenaline, and to some extent functional inactivation of serotonin has been achieved with neurotoxins (Breese and Traylor, 1971; Reader and Gauthier, 1984; Santiago et al, 2010; Bonito-Oliva et al, 2013). In addition, 6-OHDA has been found to reduce the number of orexin/hypocretin neurons in the LH (Cui et al, 2010; Oliveira et al, 2018). Therefore, some of the sleep abnormalities observed in rodent models of PD may depend on the loss, or impairment, of one or more of these components of the arousal system.…”
Section: Discussionmentioning
confidence: 99%